Analisis Persepsi Siswa Terhadap Penggunaan Website Testportal Sebagai Alat Evaluasi Hasil Belajar Siswa pada Mata Pelajaran Informatika Kelas X - Rahman, Awani; Hidayati, Abna; Hendri, Nofri; Rahmi, Ulfia (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe students' perception of the use of the testportal website as a learning outcome evaluation tool. This type of research uses a descriptive method with a quantitative approach. The sampling technique used the purposive sampling technique and the research sample was 56 students in class X at SMA Negeri 1 Padang. The research instrument used was a questionnaire with a total of 40 questions distributed through a google form. The analysis technique used was percentage and chi squared with a significance level of 5% (=0.05). The results of the study show that first, students' perception of the use of the testportal website is good with a percentage of 76.5. Second, the testportal website as a learning outcome evaluation tool is good with a percentage of 80.33%. Third, there was a significant relationship between students' perception of the use of the testportal website and the testportal website as a tool for evaluating learning outcomes with the value of the table count of 40.12>>9488. It can be concluded that students' perception of the use of the testportal website as a tool for evaluating learning outcomes in class X informatics subjects is good